Successful primary percutaneous coronary interventions in a patient with two consecutive ST-segment elevation myocardial infarctions and dual left anterior descending artery (type IV) - Spasić, Marijan; Džudović, Boris; Rusović, Siniša; Jović, Zoran; Djurić, Predrag; Romanović, Radoslav; Djenić, Nemanja; Matunović, Radomir; Obradović, Slobodan (Vojnosanitetski pregled, 2017)
Introduction. Dual left anterior descending (LAD) artery is a very rare inherited anomaly. It can be incidentally revealed during primary percutaneous coronary intervention (pPCI) and may produce difficulties in detecting and treating the culprit lesion. Case report. We presented a 52-year-old male patient with ST-segment elevation myocardial infarction (STEMI) of inferior wall, in whom dual LAD anomaly was revealed during pPCI: a short LAD artery originated from the left main coronary artery and a long LAD artery originated from the proximal part of the right coronary artery (RCA). A bare metal stent was successfully implanted in the place of the culprit lesion in RCA and ST-segment resolution was achieved in ECG. After two hours, the patient was referred again to the catheter lab due to new STEMI of anteroseptal wall. Another bare metal stent was implanted in new infarction related artery, this time it was proximal part of the short LAD. Conclusion. Careful and correct interpretation of ECG is very helpful in detection and treatment of the culprit lesion in cases with dual LAD.
Keywords: coronary vessels; congenital abnormalities; myocardial infarction; stents; reoperation; electrocardiography